2019
DOI: 10.1176/appi.neuropsych.18060148
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Behaviors in Frontotemporal Dementia: Compulsions or Impulsions?

Abstract: Objective: The presence of repetitive behaviors is one of the core criteria for behavioral variant frontotemporal dementia (bvFTD). Patients with bvFTD often have perseverative, stereotyped, or compulsive-ritualistic behavior as an early aspect of their disorder. It is unclear whether such behaviors are related to compulsions, as in obsessive-compulsive disorder (OCD), or are part of the impulse disorder spectrum. Methods: The authors investigated early (within 3 years) repetitive behaviors among 93 well-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…The relative isolation of compulsive-repetitive symptoms as well as finding food no longer enjoyable may be related to several factors. For example, it has been suggested that repetitive symptoms in bvFTD may be isolated responses to internal or external stimuli rather than an attempt to relieve anxiety associated with compulsions (Moheb et al, 2019); thus, their relative isolation in the networks is not surprising. Cognitive mechanisms, such as breakdown of response inhibition, have been considered an endophenotype bridging compulsive and impulsive symptoms (Dalley et al, 2011;Fineberg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative isolation of compulsive-repetitive symptoms as well as finding food no longer enjoyable may be related to several factors. For example, it has been suggested that repetitive symptoms in bvFTD may be isolated responses to internal or external stimuli rather than an attempt to relieve anxiety associated with compulsions (Moheb et al, 2019); thus, their relative isolation in the networks is not surprising. Cognitive mechanisms, such as breakdown of response inhibition, have been considered an endophenotype bridging compulsive and impulsive symptoms (Dalley et al, 2011;Fineberg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In at-risk states for dementia, symptoms of impulse dyscontrol can be prodromal markers of behavioral variant frontotemporal dementia (bvFTD; Rascovsky et al, 2011) or behavioral-dysexecutive variant of Alzheimer's disease (Ossenkoppele et al, 2015). These symptoms vary in their prevalence, conceptual brevity (e.g., hyperorality is a narrower construct than aggressive tendencies), in their biological correlates, interpersonal dimensions, relationships with cognition, clinical significance and the extent to which they overlap with neighboring constructs (Bozeat, 2000;Nyatsanza, 2003;Allegri et al, 2006;García-Forero et al, 2009;Cummings et al, 2015;Rosenberg, Nowrangi, & Lyketsos, 2015;Sano et al, 2018;Ruthirakuhan, Lanctôt, Di Scipio, Ahmed, & Herrmann, 2018;Moheb et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with dementia may develop abnormal repetitive behaviors such as skin picking (13,14). Repetitive behaviors in patients with dementia are more frequently related to frontotemporal dementia as compared to other types of dementia including Alzheimer's disease and have been reported to be rather repetitive impulsions mediated by brain dysfunction than compulsions as in obsessive-compulsive disorders (15). It is hard to differentiate skin picking from itch-induced scratching when only observing behaviors or the surface of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Other anecdotally reported ritualistic behaviors are inflexible grooming or walking routines, counting and strict timekeeping as well as checking or sorting behaviors (14). However, in contrast to obsessive-compulsive disorder, these rituals are not due to compulsions in bvFTD as neither their expression nor their disruption are related to feelings of anxiety (104). Utterances during anamnesis may thus also appear stereotypic and repetitive and some patients present with additional verbal and/or simple repetitive motor tics (105).…”
Section: The Clinical Diagnostic Criteria For Bvftdmentioning
confidence: 99%